La renaturation des sols des écoles parisiennes au prisme des services écosystémiques : élaboration d’un outil d’aide à la décision dans le cadre du programme cours Oasis de la ville de Paris - Fanny Delaunay; Aurélien Ramos; Xavier Lagurgue; Sophie Blanc; Nathalie Machon; Édith Akiki (Projets de Paysage)
The management of school grounds today is guided primarily by considerations of a functional nature. How can ecological issues be reconciled with the way school grounds are used and managed? Based on a field study on the ecosystemic condition of school grounds and the socio-recreational and pedagogical practices developed within this environment, we present the role played by school-ground soils and how this role can be taken into account in redefining educational projects. This article seeks shed light on potential tools and methods for evaluating the ecosystemic impact of schools. To achieve this objective a collective study was conducted between 2019 and 2022 on the Oasis School project initiated by the city of Paris within the framework of the "RECRÉ" research programme.